Strategic triangles reshaping international relations in East asia - Rozman, Gilbert (Politics in Asia series., 2022)
"Rozman shows how East Asia's international relations can be best understood through the lens of triangles, analyzing relations between the key nations through a series of trilateral relationships. He argues that triangles present a convincing answer to the question of whether we are entering a new era of bipolarity like the Cold War, or an age of multipolarity. Triangulation emerged as a dynamic in East Asia in the aftermath of the Cold War, but has been accelerated in the wake of the Xi and Trump administrations. Even as Sino-US competition and confrontation deepens, triangles have a substantial presence. East Asian triangles share an unusual mixture of three distinct elements: deep-seated security distrust; extraordinary economic interdependence; and a combustible composition of historical resentments and civilizational confidence. The combination of the three makes the case for triangularity more compelling, Rozman argues. The legacy of communism, the pursuit of reunification on the Korean Peninsula, and moves to expand beyond the US-Japan alliance have all driven the way triangles have evolved. Rozman evaluates each key triangle of states in turn and assesses how the relationship impacts the region more widely. An essential framework for understanding the current state and trajectory of East Asian International relations, for students and policy-makers"--